Extraction And Phytochemical Screening of Ethanol Extract And Simplicia of Moringa Leaf (Moringa Oleifera Lam.) From Sidikalang, North Sumatera - Ricky Andi Syahputra; Ani Sutiani; Pasar Maulim Silitonga; Zulmai Rani; Amelia Kudadiri (Publisher Cv. Inara, 2021)
Moringa leaf is a plant that has many uses that comes from the family Moringaceae and it is a tropical plant that is familiar to Indonesian people. Pharmacologically, this plant extract is reported to have antimicrobial and fungicide and it is rich in antioxidants. This metabolite compound contained in Moringa leaves has the potential as an antioxidant, antibacterial, functional and others. This study aims to determine the simplicia characterization of Moringa leaves and to determine the secondary metabolites contained in Moringa leaves, both Moringa leaf powder and Moringa leaf extract. The method of this research is experimental including the simplicia making and ethanol extract of Moringa leaves by maceration method, simplicia characterization and phytochemical screening. The results of the simplicia characterization of Moringa leaves for ethanol soluble extract content was 10,9% and water-soluble extract content was 15,8%, ash content was 9,6% and acid insoluble ash content was 0,6% and water content was 8%. The results of this study also showed that the simplicia powder and ethanol extract of Moringa leaves contained flavonoid, tannin, alkaloid, steroid and saponin.